Tinjauan Penggunaan Kartu Identitas Berobat dan Lama Waktu Penyediaan Dokumen Rekam Medis Pasien Rawat Jalan Lama Di RSUD H. DAMANHURI BARABAI Tahun 2013 - Apit Widiarta; Bibing Hendro L; Rini Astuti; STIKES Husada Borneo; Alumni STIKES Husada Borneo (Jurnal Kesehatan Indonesia, 2014)
Introduction : One of the Hospital Minimum Standards Unit at the Medical Record is time providing out patient medical record documents, the time spent registering patients ranging from medical records supplied to or discovered by officers. One of the things that affects the future is the use ofMedication Identification Card, identification card which must be taken every patient treated at the hospital. In the out patient Registration of RSUD H.Damanhuri Barabai still using the manual system where if a patient does not take long out patient Medication Identification Card, which will require a long processing the search for medical record number. This research aims to determine the use of identity cards and long treatment time ensuring provision of out patient old medical records in RSUD H.Damanhuri Barabai In 2013.Method : This research uses descriptive research method. Samples were taken with accidental sampling technique as much as 93 out patients old from date of June 17 to June - 22 June Data collection techniques of observation and interviews with research instruments such as interview guides, and observation.Result : Results reveal future provision of medical record documents out old patients who do not carry Identity Card Medication was appropriate as many as 31 people, the provision time of medical record documents a long out patients is 8.7 minutes while 9 people of time ensuring provision of out patient medical recordis10.6 minutes long. Of the 62 samples that carry Identity Card Medication average time ensuring provision of out patient medical record is 5.7 minutes long.Conclusion : Difference in time provision of medical record documents the old out patients who do not carry the Identity Card and carry Identity Card Medication Medication is 3.5 minutes.